2016
DOI: 10.1371/journal.pone.0151899
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Overall Radiotherapy Time on Clinical Outcome of Patients with Nasopharyngeal Carcinoma; A Retrospective Study

Abstract: PurposeIn Yogyakarta, nasopharyngeal carcinoma (NPC) shows a poor response to radiotherapy treatment. Previous study showed a prolonged overall treatment time (OTT), due to interruptions during treatment. This study explores the association between clinical outcome and OTT. Secondary, the relation between clinical outcome and disease stage, waiting time to radiation (WT) and chemotherapy schedule was explored.MethodsIn this retrospective cohort, 142 patients who started curative intent radiotherapy for NPC bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Univariate Cox analysis showed a significant hazard for poor local regional control and disease-free survival when the waiting time increased to >130 days. There was no association between long waiting time and OS (29).…”
Section: Discussionmentioning
confidence: 69%
“…Univariate Cox analysis showed a significant hazard for poor local regional control and disease-free survival when the waiting time increased to >130 days. There was no association between long waiting time and OS (29).…”
Section: Discussionmentioning
confidence: 69%
“…Preoperative chemoradiotherapy results in fewer than 50% of rectal cancer patients achieving complete pathological response . Response to radiation is considered to be a key factor in the success of radiotherapy, but the response to radiation is determined by multifactorial etiologies (tumor pathologic type, tumor volume, tumor hypoxia, clinical stage, radiation dose and radiation modes) . Until now, no valid radiosensitizing target has been unambiguously identified to have prognostic or predictive value for colorectal cancer radiotherapy, although a few potential molecular markers, including EGFR, KRAS/NRAS, BRAF, PTEN and PIK3CA, have been investigated; the role they played in radiotherapy remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the treatment outcomes of patients with nasopharyngeal cancer in Indonesia (Adham et al, 2014;Stoker et al, 2016;Wildeman et al, 2013). Stoker et al, (2016) retrospectively investigated the outcomes of 142 nasopharyngeal cancer patients treated with radiotherapy with or without chemotherapy with curative intent. The 2 year OS was 58% for this cohort that predominantly contained stages III-IVB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, defining the patterns of care and treatment outcomes of patients with nasopharyngeal cancer in Indonesia is important to improve the outcome of this disease worldwide. However, there are few reports on the outcomes of patients with nasopharyngeal cancer treated in Indonesia (Adham et al, 2014;Stoker et al, 2016;Wildeman et al, 2013). Furthermore, the available studies are based on a small sample size, and they may not reflect the actual clinical situation in the country.…”
Section: Introductionmentioning
confidence: 99%